Strategi Pemberdayaan Anggota Kelompok Jasema di Kalurahan Terong Kapanewon Dlingo Kabupaten Bantul - Nurul Oktaviani, Oktarina Albizzia (Program Studi Pembangunan Masyarakat Desa (D3), 2022)
One way to strengthen the agricultural sector is to form groups that care about the agricultural sector, one example is the forest farmer group. This research was conducted at the Sengon Mahogany Forest Farmers Group